2000
DOI: 10.1063/1.480847
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and dynamics of O(3P)+CO(1Σ+) collisions

Abstract: Electronic to vibrational and rotational energy transfer in S ( 1 D)+ CO quenching reaction: Ab initio MO and surface hopping trajectory studies A new He-CO interaction energy surface with vibrational coordinate dependence. II. The vibrational deactivation of CO (v=1) by inelastic collisions with 3 He and 4 He The potential energy surfaces of the three lowest electronic triplet states of CO 2 which lead to O( 3 P)ϩCO( 1 ⌺ ϩ ), 3 AЈ, 1 3 AЉ, and 2 3 AЉ, have been computed at the completeactive-space-self-consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 26 publications
6
41
0
Order By: Relevance
“…Comparison with other works calculating the low lying СО 2 states showed that energies agree well with the results of [2][3][4][5] given in Table 2. The values of obtained by us for the 3 B 2 and 3 A 2 electronic states are close to the data of [2], while our results for 1 A 2 are close to those of [4].…”
Section: Discussion Of Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Comparison with other works calculating the low lying СО 2 states showed that energies agree well with the results of [2][3][4][5] given in Table 2. The values of obtained by us for the 3 B 2 and 3 A 2 electronic states are close to the data of [2], while our results for 1 A 2 are close to those of [4].…”
Section: Discussion Of Resultssupporting
confidence: 86%
“…The electronic states (both ground and excited) of the СО 2 molecule were the subjects of previous studies [1][2][3][4][5][6]. However, the authors of many calculations per formed using quantum chemistry methods frequently use experimental data mainly for comparing the min ima of calculated potential energy surfaces (PESs) and the vibrational frequencies of different modes.…”
Section: Introductionmentioning
confidence: 99%
“…The dissociation energy for 1 B 2 state is 2.01 eV which also agrees with the experiment value 1.73 eV within range of error. About the dissociation energy for 3 B 2 state, our result is 0.94 eV, which is sup ported by Braunstein and Duff's theoretical result [24] of 0.94 eV.…”
Section: Results and Discussion Equilibrium Geometries Adiabatic Exsupporting
confidence: 84%
“…The adiabatic excitation energy of 3 B 2 , 3 A 2 , 1 A 2 , and 1 B 2 states had been reported by many experimen tal and theoretical researchers [16,17,23,24]. How ever, as a result of the limitation of conditions of experiment and calculation, the results are not very accurate.…”
Section: Results and Discussion Equilibrium Geometries Adiabatic Exmentioning
confidence: 98%
“…To calculate the tunnelling probability for the O( 3 P) + CO reaction we started with the analytical PES of Braunstein & Duff (2000) based on CASPT2 calculations on the lowest 3 A′ electronic state. However, this PES has an artificially deep van der Waals well (1440 K) at the wrong (non‐linear) geometry, which is probably an artefact of the fitting.…”
Section: Computational Methodologymentioning
confidence: 99%